2009
DOI: 10.1152/ajpregu.00119.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of SLC12A10.2, a Na-Cl cotransporter-like protein, in a Cl uptake mechanism in zebrafish (Danio rerio)

Abstract: The thiazide-sensitive Na(+)-Cl(-) cotransporter (NCC), a member of the SLC12 family, is mainly expressed in the apical membrane of the mammalian distal convoluted tubule (DCT) cells, is responsible for cotransporting Na(+) and Cl(-) from the lumen into DCT cells and plays a major role in the mammalian renal NaCl reabsorption. The NCC has also been reported in fish, but the functional role in fish ion regulation is yet unclear. The present study used zebrafish as an in vivo model to test the hypothesis of whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 42 publications
9
170
1
Order By: Relevance
“…Double ISH and ICC experiments demonstrated specific expression of zNCCg mRNA in a novel type of ionocyte, NCC cells, which differ from the previously reported HR and NaR cells (Fig. 2C,D), and loss-of-function experiments with zNCCg morpholinos revealed significant decreases in both Cl -influx and Cl -content in the morphants (Wang et al, 2009). These results indicate the function of NCC cells, in which zNCCg may be the major player in the apical Cl --uptake pathway, although ICC localization of the zNCCg protein in zebrafish NCC cells remains to be confirmed.…”
Section: Ncc Cells Apical Ncccontrasting
confidence: 93%
“…Double ISH and ICC experiments demonstrated specific expression of zNCCg mRNA in a novel type of ionocyte, NCC cells, which differ from the previously reported HR and NaR cells (Fig. 2C,D), and loss-of-function experiments with zNCCg morpholinos revealed significant decreases in both Cl -influx and Cl -content in the morphants (Wang et al, 2009). These results indicate the function of NCC cells, in which zNCCg may be the major player in the apical Cl --uptake pathway, although ICC localization of the zNCCg protein in zebrafish NCC cells remains to be confirmed.…”
Section: Ncc Cells Apical Ncccontrasting
confidence: 93%
“…2). The kidney expression of NCC is weak in winter flounder (seawater fish) (16), but strong in European eel (euryhaline fish) and zebrafish (freshwater fish) (11,54). These results suggest that NCC in the kidney is essential for fish to live in freshwater but not seawater, and there is a relationship between renal expression of NCC and the adaptability of pufferfish to freshwater.…”
Section: Discussionmentioning
confidence: 94%
“…The gill is another important osmoregulatory tissue in teleosts. Recently, a fish-specific isoform of NCC was identified that is specifically expressed in the mitochondrion-rich cells of the gill epithelium and appears to be involved in Na ϩ and Cl Ϫ uptake in certain freshwater fish species (21,24,54). No gene encoding this fish-specific NCC was identified in the mefugu genome (Fig.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…and Cl 2 uptake function [6,8], resulted in the upregulation of cgrp mRNA expression (figure 1b); in addition, CGRP loss-offunction stimulated the expression of Cl 2 transporters (figure 2e) and Cl 2 influx ( figure 5). As the use of CALC morpholinos does not allow us to distinguish between the effects of CT and CGRP loss-of-function, we also performed specific CGRP gain-of-function experiments: cgrp overexpression suppressed both the expression of ncc2b mRNA (figure 4) and Cl 2 influx ( figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…These findings inspired us to test the hypothesis that CGRP is involved in the control of fish body fluid Cl 2 homeostasis. The expression and function of Cl 2 transporters have been well studied in zebrafish, because of the comprehensive genetic databases and well-developed molecular physiological approaches available for this organism [6,8]. In zebrafish embryos, the skin ionocytes are responsible for the majority of ion regulation until 7-14 days post-fertilization (dpf ), at which time the gills are fully developed and functional [24].…”
Section: Introductionmentioning
confidence: 99%